ARE MORAL VALUES OVERRIDING? HOW BEAUTY CHALLENGES ROBERT ADAMS'S THEORY OF VALUE. Issue 4 (1st February 2022) - Jakobsen, Martin
Abstract: This article addresses the following meta‐ethical question: do moral values have a special position among other values? According to Robert Adams, moral values do have a special position and are of overriding importance. I argue that the "overridingness" thesis is inconsistent with Adams's value theory that only God has value in himself and all other things are valuable to the extent that they resemble God. I consider some possible ways of integrating the overridingness thesis that are latent in Adams's work and argue that none succeeds. My main contribution is to propose a solution to the inconsistency in Adams's theory. I argue that a theological account of beauty gives us reason to reject the overridingness thesis. Morality overrides some other concerns, but not all other concerns.